Research installation for growing plants in a high voltage electric field and under various optical radiation - Chervinsky, L.; Makoda, O. (Energy and Automation, 2025)
The study of the influence of high-intensity electric fields and various optical radiation on plant growth and development is a promising direction in agronomy and agroecology. The aim of this work is to develop and test an experimental setup that allows creating controlled conditions for growing plants under the influence of electric fields and optical radiation of various spectra. The setup consists of a system for creating high-intensity electric fields, LED light sources, a climate chamber, and a monitoring and data analysis system for recording growth parameters and physiological processes of plants. The main goal of the study is to assess the effectiveness of the influence of these factors on photosynthetic activity, growth rate and plant yield, as well as to determine the optimal parameters for stimulating their development. Experiments have shown that electric fields can significantly increase the growth rate of plants, and light spectra (red, blue, ultraviolet) affect the efficiency of photosynthesis and the development of the root system. In addition, the combined effect of electric fields and optical radiation helps to improve crop yield and plant resistance to stress factors such as diseases, pests and extreme climatic conditions. High-voltage electric fields also play an important role in stimulating plant growth. The effect of electric fields on biological objects is widely studied in various fields of science, in particular in agronomy. It has been established that electric fields can affect plant growth by stimulating ionic and electrochemical processes in cells, which improves the absorption of water and nutrients from the soil. This opens up new opportunities for improving the quality and quantity of the crop. Key words: electrotechnological complex, energy efficiency, high-voltage electric field, automation